Critical success factors in learning English pronunciation: a look through the lens of the learner - Dao, Duc Nguyen Anh (2021)
It is beyond dispute that developing good pronunciation is crucial to successful second language learning (Dickerson, 2019; Sugimoto & Uchida, 2018; Yates, 2017). However, until recently, compared with other fields of SLA, not much has been understood about how L2 pronunciation can be taught and learned effectively, and more importantly, learners’ perspectives on L2 pronunciation related issues still have considerably low visibility in research.